The Effect of Transformational Leadership on Innovative Behavior of Lecturers in Online Learning Mediated by Psychological Climate - Valentina Happy Vanesa; Anastasia M.D. Batmomolin; Tri Hananto; Sarfilianty Anggiani (Budapest International Research and Critics University, 2022)
The COVID-19 pandemic has challenged the world of education, especially vocational education. This quantitative study aims to examine the effect of transformational leadership on the innovative behavior of lecturers in online learning during the COVID-19 pandemic mediated by the psychological climate. Collecting data used a questionnaire distributed through google form. Respondents involved in the study were 132 lecturers in the health sector. The data was processed using the structural equation modeling partial least square (SEM PLS). The results show that transformational leadership has a positive effect on the psychological climate, psychological climate has a positive effect on innovative behavior and mediates the effect of transformational leadership on lecturers' innovative behavior. The psychological climate created in universities or colleges, in terms of leader support, role clarity, contribution, recognition, self-expression and challenges experienced by lecturers greatly affect the functioning of transformational leadership in promoting innovative behavior of lecturers.